2018
DOI: 10.5468/ogs.2018.61.4.431
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian tissue cryopreservation and transplantation in patients with cancer

Abstract: Chemotherapy and radiotherapy improved survival rates of patients with cancer. However, they can cause ovarian failure and infertility in women of reproductive age. Infertility following cancer treatment is considered a major quality of life issue. Ovarian tissue cryopreservation and transplantation is an important option for fertility preservation in adult patients with cancer who need immediate chemotherapy or do not want to undergo ovarian stimulation. Ovarian tissue freezing is the only option for preservi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 97 publications
2
66
0
Order By: Relevance
“…Although the survival rate of cancer patients has dramatically improved due to development of chemotherapy, ovarian toxicity induced by chemotherapy is a major complication. Gonadotoxic chemotherapy during reproductive age can lead to iatrogenic primary ovarian insufficiency (POI), and loss of follicular reserve that depends on the type, dose, duration, and combination of chemotherapeutic agents, and disease stage, as well as patient age [ 14 , 15 ]. It has been reported that 53–89% of chemotherapy-induced POI occurs in patients with breast cancer [ 16 ].…”
Section: The Effect Of Chemotherapy On Ovarian Functionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the survival rate of cancer patients has dramatically improved due to development of chemotherapy, ovarian toxicity induced by chemotherapy is a major complication. Gonadotoxic chemotherapy during reproductive age can lead to iatrogenic primary ovarian insufficiency (POI), and loss of follicular reserve that depends on the type, dose, duration, and combination of chemotherapeutic agents, and disease stage, as well as patient age [ 14 , 15 ]. It has been reported that 53–89% of chemotherapy-induced POI occurs in patients with breast cancer [ 16 ].…”
Section: The Effect Of Chemotherapy On Ovarian Functionmentioning
confidence: 99%
“…Oocyte cryopreservation, like embryo cryopreservation, is considered a gold standard technique for fertility preservation in cancer patients [ 15 , 73 ]. In 2000, the United Kingdom (UK) Human Fertilization and Embryology Authority (HFEA) allowed the use of frozen oocytes for fertility preservation [ 74 ].…”
Section: Fertility Preservation Optionsmentioning
confidence: 99%
See 3 more Smart Citations